Dendrite‐Free Lithium Anodes with Ultra‐Deep Stripping and Plating Properties Based on Vertically Oriented Lithium–Copper–Lithium Arrays. Issue 29 (30th May 2019) - Cao, Zhenjiang; Li, Bin; Yang, Shubin
Abstract: Although lithium metal is the best anode for lithium‐based batteries, the uncontrollable lithium dendrites especially under deep stripping and plating states hamper its practical applications. Here, a dendrite‐free lithium anode is developed based on vertically oriented lithium–copper–lithium arrays, which can be facilely produced via traditional rolling or repeated stacking approaches. Such vertically oriented arrays not only enable both the lithium‐ion flux and the electric field to be regulated, but also can act as a "dam" to guide the regular plating of lithium, thus efficiently buffering the volume change of the lithium anode upon cycling. As a consequence, the vertically oriented anode exhibits an excellent deep stripping and plating capability upto 50 mAh cm −2, high rate capabilities (20 mA cm −2 ), and long cycle life (2000 h). Based on this anode, a full lithium battery with a LiCoO2 cathode delivers a good cycle life, holding great potential for practical lithium‐metal batteries with high energy densities. Abstract : Vertically oriented lithium–copper–lithium arrays are facilely produced to efficiently inhibit the growth of dendrites especially under deep stripping and plating states, since such unique geometry enables both the lithium‐ion flux and the electron field to be regulated, guiding the regular stripping and plating of lithium. This provides a potential for practical applications for lithium‐based batteries with high energy densities.